Fluorescence-Guided High-Grade Glioma Surgery More Than Four Hours After 5-Aminolevulinic Acid Administration - Maragkos, Georgios A.; Schüpper, Alexander J.; Lakomkin, Nikita; Sideras, Panagiotis; Price, Gabrielle; Baron, Rebecca; Hamilton, Travis; Haider, Sameah; Lee, Ian Y.; Hadjipanayis, Constantinos G.; Robin, Adam M. (Frontiers in Neurology, 2021)
Background: Fluorescence-guided surgery (FGS) using 5-aminolevulic acid (5-ALA) is a widely used strategy for delineating tumor tissue from surrounding brain intraoperatively during high-grade glioma (HGG) resection. 5-ALA reaches peak plasma levels ~4 h after oral administration and is currently approved by the FDA for use 2–4 h prior to induction to anesthesia. Objective: To demonstrate that there is adequate intraoperative fluorescence in cases undergoing surgery more than 4 h after 5-ALA administration and compare survival and radiological recurrence to previous data. Methods: Retrospective analysis of HGG patients undergoing FGS more than 4 h after 5-ALA administration was performed at two institutions. Clinical, operative, and radiographic pre- and post-operative characteristics are presented. Results: Sixteen patients were identified, 6 of them female (37.5%), with mean (SD) age of 59.3 ± 11.5 years. Preoperative mean modified Rankin score (mRS) was 2 ± 1. All patients were dosed with 20 mg/kg 5-ALA the morning of surgery. Mean time to anesthesia induction was 425 ± 334 min. All cases had adequate intraoperative fluorescence. Eloquent cortex was involved in 12 cases (75%), and 13 cases (81.3%) had residual contrast enhancement on postoperative MRI. Mean progression-free survival was 5 ± 3 months. In the study period, 6 patients died (37.5%), mean mRS was 2.3 ± 1.3, Karnofsky score 71.9 ± 22.1, and NIHSS 3.9 ± 2.4. Conclusion: Here we demonstrate that 5-ALA-guided HGG resection can be performed safely more than 4 h after administration, with clinical results largely similar to previous reports. Relaxation of timing restrictions could improve procedure workflow in busy neurosurgical centers, without additional risk to patients.